(3RjGOI eKdKGJ bWQHs - (3eMeO Hf MHjH Hf CejI Hf YeQh GdgGTej, HGdhdGA, CHh LYaQ GdHZOGOj, ef ehGdj Hfj GdYHGS,J (B245 (3g` s
(3ChdgG (B:s
(3GdCd hGdCd hGdCd hCeG GdCd bGd Gddg YR hLd (B:" (3dGjQbHhf ai eDef EdG hdGPeI s
(3BNQgG (B:s
(3GdbHGdI hGdbHGdI hGdbHGdI hCeG GdbHGdI HGdVe aGdMPGA MPGA hLgd ,Ci bHGdI hLgc s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B78 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B174s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs